Síndrome metábolico y su relación con la funcionalidad familiar en los pacientes atendidos en la consulta de medicina familiar, Santa Rosa 2016. - Blacio Leon, Lixeth Paola (2017)
The metabolic syndrome (SM) is a serious issue for public health and implies a higher risk to suffer from coronary and cerebrovascular disease. The issue for public health at the moment, is that it affects more in younger ages; it is estimated that over a million of adolescents in the United States are affected. The increase of the MS is due to unhealthy lifestyles, which start in the family. The objective of this research is to analyse the functionality of family and its relation with the metabolic control in patients with metabolic syndrome from the health center in Santa Rosa; and to distinguish sociodemographic, clinical and biochemical aspects. The study is descriptive, analytic and correlational, with a cross-sectional design, directed to 640 patients with hypertension and diabetes mellitus type 2 and a random sample of 150 patients with metabolic syndrome, who passed a full clinical evaluation and known glucose levels when fasting, triglycerides, HDL cholesterol, they also took the family functionality test (FFSIL). The MS diagnosis was completed as stated in the IDF 2009. The results were analysed by a statistical test of the Chi², value of p, of Cramer´s V and the Odds Ratio with an IC of 95%. It was determined that 99% of the patients with metabolic syndrome, who belonged to a dysfunctional family had no control over one or more aspects, the OR and confidence levels do not have a statistical significance. In conclusion, dysfunction in families does not affect statistically the metabolic control of patients with MS. Keywords: Metabolic control, Diabetes Mellitus, Obesity, Hypertension, Family functionality.